2020
DOI: 10.1177/1071100720959023
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of All-Soft Suture Anchor Single-Row vs Double-Row Bridging Construct for Insertional Achilles Tendinopathy

Abstract: Background: Two common operative fixation techniques for insertional Achilles tendinopathy are the use of all-soft suture anchors vs synthetic anchors with a suture bridge. Despite increasing emphasis on early postoperative mobilization, the biomechanical profile of these repairs is not currently known. We hypothesized that the biomechanical profiles of single-row all-soft suture anchor repairs would differ when compared to double-row suture bridge repairs. Methods: Achilles tendons were detached from their ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…For example, Beitzel et al (33) concluded that the double-row technique has a greater contact area and tolerates greater tension in stress testing than the single-row technique, which corroborates the results of a previous study by an orthopedic implant company (34) . However, a recent cadaver study (35) , as well as Pilson et al (36) , found that the double-row technique could not tolerate a greater load before failure.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Beitzel et al (33) concluded that the double-row technique has a greater contact area and tolerates greater tension in stress testing than the single-row technique, which corroborates the results of a previous study by an orthopedic implant company (34) . However, a recent cadaver study (35) , as well as Pilson et al (36) , found that the double-row technique could not tolerate a greater load before failure.…”
Section: Discussionmentioning
confidence: 98%
“…15 Sutures tearing through tendon in biomechanics has historically been recognized as a common failure mode in both single-and double-row Achilles repairs. 2,6,8,14,18 However, this failure is not frequently seen clinically. Clinically, a complication repeatedly reported is postoperative superficial wound infection treated with antibiotics and debridement.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that single-row repair is similar to the double-row suture bridge technique in terms of load to failure and cyclic displacement, which is not significantly associated with the size of the rotator-cuff rupture [ 20 ]. A biomechanical study found that the Achilles insertion repaired by the double-row technique had less displacement during cyclic loading but could not stand more load before clinical failure than single-row suture anchoring [ 6 ]. However, a meta-analysis consisting of eight biomechanical studies suggested that double-row repair is superior to single-row repair in load to failure and tear resistance in rotator cuffs [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Achilles insertion is usually repaired by reattaching the tendon to the calcaneus using anchors and sutures. Suture anchors include single-row and double-row repair, which each have advantages and disadvantages in biomechanical properties [ 6 , 7 ]. The double-row suture bridge technique has been increasingly used in recent years.…”
Section: Introductionmentioning
confidence: 99%